PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE TAKE AND GIVE TERHADAP HASIL BELAJAR SISWA PADA SUBTEMA 1 SUMBER ENERGI KELAS IV SD NEGERI 091273 KARANG BANGUN - Lidia Esra Purba; Janwar Tambunan; Esti Sirait (CV. KAMPUS AKADEMIK PUBLISING, 2023)
The study aims to determine whether there is an effect of the Take and Give Type of Cooperative Learning Model on Student Learning Outcomes in Sub-theme sub-theme 1 Energy Sources Class IV SD Negeri 091273 Karang Bangun Academic Year 2023/2024. This research is a quantitative study using an experimental method. The population of this study were all 24 students of class IV SD Negeri 091273 Karang Bangun and 24 students were the samples in this study. The instruments used were pretest and posttest tests which had been tested for validation and reliability. The results showed that there was an influence of the take and give cooperative learning model on student learning outcomes in Sub-theme 1 Energy Sources Class IV SD Negeri 091273 Karang Bangun in the 2023/2024 academic year. Based on the analysis of the posttest value data using the t-test, it can be tcount > ttable, namely with a value of 14,497>2,073, then Ha is accepted and H_0 is rejected so that it can be interpreted that there is an influence of the take and give type of cooperative learning model on Student Learning Outcomes in Sub-theme 1 Energy Sources Class IV SD Negeri 091273 Karang Bangun.